Disentangling the roles of bottom‐up and top‐down drivers in the trade‐off between food acquisition and safety in prey with multiple predators. (20th November 2020) - Pays, Olivier; Blanchard, Pierrick; Chamaillé‐Jammes, Simon; Valeix, Marion; Loveridge, Andrew J.; Macdonald, David W.; Périquet, Stéphanie; van der Meer, Esther; Duncan, Patrick; Mtare, Godfrey; Fritz, Hervé
Abstract: Prey face a trade‐off between acquiring food and avoiding predation, but food availability, and therefore its effect, is rarely measured in field studies investigating non‐lethal effects of predation. The main aim of this study was to investigate the role of the presence of predators in the functional adjustments of feeding parameters with patch quality in a medium‐sized herbivore. In Hwange National Park (Zimbabwe), we set up an experiment by manipulating, over two years, patch quality for impala Aepyceros melampus, a medium‐sized herbivore. We assess predation risk by monitoring the presence of three GPS‐equipped predators: African lions Panthera leo, spotted hyaenas Crocuta crocuta and African wild dogs Lycaon pictus . In enriched, fertilised plots the impalas reduced step rates (i.e. the rates of change in feeding stations), and increased their number of bites per feeding station while bite rates were not affected. Thus, the main adjustment of their feeding was the step rate. The total time the impalas spent vigilant appeared to be a good predictor of the variation of their bite rate. Although vigilance caused a reduction in bite rate when at a feeding station, the impalas reduced the relative costs of vigilance by continuing chewing and processing their food when scanning for predators. When predators were in the vicinity, the impalas increased their exclusive vigilance (high‐cost vigilance) but not their vigilance while chewing (low‐cost vigilance) and decreased their bite rate while their step rate and the number of bites per feeding station did not change significantly. The impalas were thus visually disconnected from their patch, and reduced their bite rate when actually foraging. Exclusive vigilance increased when both lions and hyaenas were in the vicinity, and when wild dogs were nearby. Patterns of vigilance that altered bite rate were linked to the presence of predators during the previous 24 hr. Over the long term patch quality was the main determinant of the feeding parameters (step rate and bite rate). This study shows how predators, by affecting the time prey devote to predator detection, shape the functional adjustments of food acquisition by prey to local patch quality. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.